Effectiveness of Wastewater Treatment Installation and Liquid Waste Quality in Dr. Soetomo General Hospital, Surabaya - I'anatul Ulya Dewi; R Azizah; Zida Husnina; Arif Sumantri; Nurul Qomariah; Suhariono Suhariono; Siti N. A. Jauharoh; Mohd Latif (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Hospitals are institutions that produce liquid waste that may pollute the environment and have a dangerous impact on health. Hospital waste has the potential to contain hazardous chemicals, pharmaceutical waste, radioactivity and microbiological pathogens in liquid waste that can pollute the environment and disrupt the balance of the ecosystem. This study aims to determine the effectiveness of the Wastewater Treatment Plant (WWTP) and the quality of the liquid waste at the Dr. Soetomo General Hospital. Methods: This research was a quantitative descriptive study using secondary data from laboratory analysis of wastewater inlet and outlet of The Central Wastewater Treatment Plant (WWTP) of Dr. Soetomo General Hospital for the January-December 2020 period. Effectiveness was obtained by calculating the difference between the inlet and outlet values of each parameter divided by the inlet value multiplied by 100%. Results and Discussion: WWTP in Dr. Soetomo General Hospital Surabaya used a central WWTP which had 3 (three) units, namely WWTP Sequence Batch Reactor (SBR), WWTP Membrane Biostrain Reactor (MBR) and WWTP Aerobic Biofilter which aims to improve the quality of liquid waste. Based on the results of the research analysis, it has been found that hospital wastewater treatment using a central WWTP system is effective for reducing the levels of parameters, namely Total Suspended Solid (TSS) by 60.55%, Biological Oxygen Demand (BOD) by 72.52%, Chemical Oxygen Demand (COD) by 54.02%, Ammoniacal Nitrogen (NH3N) by 90.91%, Phospate (PO4) by 71.43%, bacteria group E. Coli by 99.93%. The temperature and Potential of Hydrogen (pH) parameters recorded at the outlet are in accordance with the established quality standards. Conclusion: The three WWTP units used in Dr. Soetomo General Hospital are able to treat liquid waste effectively. Liquid waste at each outlet parameter is in accordance with East Java Governor Regulation No. 72 of 2013 concerning quality standards for health facilities waste water, so that the effects of contamination on the environment can be minimized.